Cupping Therapy for Anemia in Women: A Scoping Review - Tulus Agreena; Mohammad Hakimi; Dhesi Ari Astuti (Journal La Medihealtico, 2025)
Anemia remains a major public health problem among women of reproductive age worldwide, particularly in developing countries such as Indonesia. Limitations of conventional anemia management, including adherence issues and side effects of iron supplementation, have encouraged interest in complementary therapies such as wet cupping therapy (WCT). This study aimed to systematically map existing empirical evidence on the effects of wet cupping therapy on hemoglobin levels and hematological parameters in women through a scoping review approach. The review was conducted following the PRISMA-ScR guidelines. Literature searches were performed across multiple databases, including PubMed, Scopus, Google Scholar, and institutional repositories, resulting in 312 identified records. After screening and eligibility assessment, six studies published between 2016 and 2023 were included. The selected studies employed diverse designs, including experimental clinical trials, quasi-experimental, pre–post, cross-sectional, prospective cohort, and retrospective observational studies, with sample sizes ranging from 17 to 364 female participants. Across all studies, wet cupping therapy was associated with either maintenance or improvement of hemoglobin levels, as well as favorable changes in iron, total iron-binding capacity, and other biochemical parameters. No evidence indicated that WCT caused anemia when administered appropriately. Overall, the findings suggest that wet cupping therapy may serve as a safe and potentially beneficial complementary intervention for improving hematological status in women. However, further research using randomized controlled trials and standardized intervention protocols is required to establish its clinical effectiveness and inform evidence-based practice.